2011
DOI: 10.1073/pnas.1103845108
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of the role of chromatin interactions in long-range action of enhancers and insulators

Abstract: Long-distance regulatory interactions between enhancers and their target genes are commonplace in higher eukaryotes. Interposed boundaries or insulators are able to block these long-distance regulatory interactions. The mechanistic basis for insulator activity and how it relates to enhancer action-at-a-distance remains unclear. Here we explore the idea that topological loops could simultaneously account for regulatory interactions of distal enhancers and the insulating activity of boundary elements. We show th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 57 publications
5
36
0
Order By: Relevance
“…In mechanism 1, termed brachiation, transient internucleosomal interactions mediated by histone tails could keep chromatin arrays or fibers in close proximity and allow relocation of the interacting partners relative to each other at a high rate. In mechanism 2, termed transient collapse, multiple intrafiber interactions mediated by histone tails could be fully disrupted and reestablished in a different register (36). this case it is unclear how the target promoter is identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mechanism 1, termed brachiation, transient internucleosomal interactions mediated by histone tails could keep chromatin arrays or fibers in close proximity and allow relocation of the interacting partners relative to each other at a high rate. In mechanism 2, termed transient collapse, multiple intrafiber interactions mediated by histone tails could be fully disrupted and reestablished in a different register (36). this case it is unclear how the target promoter is identified.…”
Section: Discussionmentioning
confidence: 99%
“…3B, mechanism 1) or by reestablishing internucleosomal interactions de novo (Fig. 3B, mechanism 2) (36).…”
Section: Enhancer Action In Chromatinmentioning
confidence: 99%
“…Further experiments are needed to confirm the involvement of DNA supercoiling in the loop interference we measured in vivo. Of particular interest is whether the prevalent DNA supercoiling in eukaryotic genomes (61) plays a role in the efficiency and specificity of enhancer-promoter contact, or whether more complex mechanisms such as nucleosome-nucleosome interactions are also involved (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…Several models have been proposed to describe how enhancers may communicate with their target gene promoter [112]. Currently the most plausible model supported by both theoretical [113] and experimental [114,115] observations is the "looping" model in which the remote enhancer "loops out" the intervening DNA to reach the target promoter. It was shown that the formation of these chromatin loops depends on sequence-specific TFs bound to the enhancer and the promoter [115].…”
Section: Diverse Promoter Architectures Enable Complex Regulatory Lanmentioning
confidence: 99%